CRITICAL DISCOURSE ANALYSIS AND CULTURE OF SEKEPENG DANCELIFE - Nova Lady Simanjuntak; Evan Wardiannata, Jonathan Salmanezer, Jasmine Ambun Sintalegawa, Sapta Lelunu, Apri Yardi, Wika Dwi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Skepeng or Lawang Skepeng dance is a custom of the Ngaju Dayak tribe in Central Kalimantan, which is a wedding dance. This dance is only used for traditional events at weddings, a kind of silat game (main manca in Dayak language) to welcome guests of honor or the bride's entourage. This dance is relevant as a literary discussion as it contains local, national and global cultural values as part of an intercultural peace space as well as a point of reflection on the values of loyalty. This research uses a data search method on secondary sources as qualitative research. The results showed that the philosophy of this Lawang Sakepeng tradition is to keep a family life away from various obstacles, hindrances and disasters. This tradition is a proof that he can make the family proud by keeping the brave bachelor.